Application of Service Service Application System in the Regional Service Agency of Gresik Regency (Study of Structural Upgrade Services) - Khobiburrohma, Eviva Nur; Hijri, Yana Syafriyana; Hadi, Krishno (Budapest International Research and Critics University, 2022)
E-Government is a form of public service implementation based on the use of information and communication technology. One of the government agencies that utilizes the sophistication of technology and information in public services is the Regional Personnel Agency of Gresik Regency. This government agency has an online system, namely